INTERFEROMATRY FOR COASTAL SPITE GEOMORPHOLOGY MAPPING - Marghany , Maged; Hashim, Mazlan
This study presents new approach for mapping coastal geomorphology changes from interferometric synthetic aperture radar (InSAR) data. Two RADARSTA-1 SAR standard beam data were processed to acquire digital elevation of surface spit topographic information from INSAR. Furthermore, Fuzzy B-spline model combined with InSAR model to obtain more precisely information. Fuzzy B-spline model implemented within unwrapped phase and the RADARSAT-1 SAR data backscattered power. The study shows that digital elevation of spit topographic map is produced with relative errors of Â± 0.2 m rms. The rate change of spit is 3 m/year. The terrain slope estimated using cross-correlation phase is agreed with ones estimated from ground field data with R2 of 0.86. This study also shows that the Fuzzy B-spline model is decreased problem of uncertainties of elevation height estimation. In conclusion, integration between INSAR procedures and Fuzzy B-spline model can be used as geomatica tool for mapping coastal geomorphology changes. In fact, combination between InSAR and Fuzzy B-spline reduced uncertainties to acceptable level of accuracy.